S117 RSIV. F/HN-mediated gene therapy enables lungs to produce therapeutically relevant levels of FVIII. (12th November 2015) - Pytel, KM; Paul-Smith, MC; McIntosh, J; Chan, M; Meng, C; Pringle, I; Davis, L; Inoue, M; Hasegawa, M; Hyde, SC; Gill, DR; Nathwani, AC; et al.
Abstract : We have previously shown that lung when treated with Sendai virus-mediated gene transfer can produce secreted proteins and release them into the circulation (Griesenbach et al., Mol Therapy 2002). Despite the high levels of transduction efficiency the gene expression is transient and repeated administration is not feasible due to induction of immune responses. To overcome these barriers we developed a lentiviral vector specifically pseudotyped with the Sendai virus envelope proteins F and HN (rSIV. F/HN) to allow efficient transduction of the airways. Stable expression for >20 months after a single dose and efficient transduction after repeated administration despite detection of anti-rSIV. F/HN neutralising antibodies make the vector an attractive candidate for a large range of disease indications. Here, we first transduced mouse lung with rSIV. F/HN carrying the secreted reporter gene Gaussia luciferase (GLux) or a control virus by nasal instillation (1e6 transduction units (TU)/mouse, n = 5 –6/group). Persistent levels of GLux expression were detectable in lung (3 logs above control) and broncho-alveolar lavage fluid (BALF, 4 logs above control) for at least 12 months. Importantly, even this modest dose of virus lead to significant (p < 0.01) levels of GLux in serum (274 ± 72 RLU/ul, control: 41 ± 6 RLU/ul) which persisted for at least 12 months further supporting the hypothesis that the lung is a suitable, non-invasive factory for production of secreted proteins. Gene therapy strategies for haemophilia have focussed on intravenous or intramuscular delivery of the gene transfer agent. Here, we treated the murine lung with rSIV. F/HN carrying the FVIII cDNA (1.6e8–3.4e8 TU/mouse, ) or placebo and assessed whether therapeutically relevant levels of FVIII can be produced. Significant (p < 0.05) and dose-related levels of FVIII were detectable in lungs and BALF 10 and 28 days post-transduction. Dose-related levels of FVIII were also detectable in plasma, which reached a therapeutically relevant level of 3% of normal 1 month after gene transfer. These data support the concept that rSIV. F/HN-mediated transduction of lungs can produce therapeutically relevant and persistent levels of recombinant protein in blood. Reference: 1 Griesenbach U, Cassady RL, Ferrari S et al . The nasal epithelium as a factory for systemic protein delivery. Mol Ther . 2002;5 :98–103